Learning Management System: Case study Effectiveness of the ADDIE Instructional Design Model in Creative Writing in EFL Students - Hindrayani, Titik; Diah Ambarumi Munawaroh (JEET, Journal of English Education and Technology, 2023)
The purpose of this study is to determine the effectiveness of the ADDIE model in online teaching in Indonesia LMS in increasing the creativity of EFL students' writing skills. The researcher used a quasi-experimental design with pre-test, post-test, and control group designs. The research topic used in this case is Sixty freshmen from English departments who were chosen at random and assigned equally to the research group. The experimental group was exposed to an e-learning environment that aims to develop students' creative writing skills, whereas the control group was exposed to traditional teaching methods. Using creative writing checklists and writing tests designed to assess specific features of creative writing (originality, accuracy, self-expression, fluency, flexibility, and overall writing performance to assess creative writing in study participants, the results of the t-test and eta square statistical test indicate the existence of a statistically significant difference between the mean scores obtained by the experimental group and those obtained by the control group. The article concludes with more conclusions and pedagogical implications.